2017
DOI: 10.1111/ggi.13050
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of depression in the empty nest elderly from the Sichuan Longmenshan fault earthquake

Abstract: Of the earthquake affected empty nest elderly, depression was highest in females and the bereaved. Further poor subjective support was found to be strong indicator of depression in this special group. To minimize depression in the vulnerable elderly, measures should be taken to assist empty nesters in the earthquake-stricken areas make full use of social support. Geriatr Gerontol Int 2017; 17: 2143-2149.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…That means we should pay more attention to old people' mental health in Anhui, China. However, there were some ndings inconsistent with previous studies [13,22]; our study revealed that no signi cant differences existed in SWB and depression between the two groups. This was an unexpected and interesting result.…”
Section: Discussioncontrasting
confidence: 99%
“…That means we should pay more attention to old people' mental health in Anhui, China. However, there were some ndings inconsistent with previous studies [13,22]; our study revealed that no signi cant differences existed in SWB and depression between the two groups. This was an unexpected and interesting result.…”
Section: Discussioncontrasting
confidence: 99%
“…The area affected by the earthquake accounted for only 11.6% of the total area of Yushu Prefecture [65]. Although six years have passed since the earthquake, we cannot rule out the association between the high depression prevalence in this study and the influence of earthquakes in a small percentage of participants [66,67].…”
Section: Prevalence Of Depression In Tibetan Adultsmentioning
confidence: 87%
“…The only other study to date on elderly earthquake victims was conducted by Xu and colleagues ( 13 ), who administered the GDS-30 to 1,783 elderly people living alone 7 years after the Wenchuan earthquake. They employed a cutoff score of 10, which is comparable with a cutoff score of 5 when using the GDS-15.…”
Section: Discussionmentioning
confidence: 99%
“…They found that reduced independence with respect to instrumental activities of daily living (IADL) was associated with a greater probability of depression. According to a recent study ( 13 ), 83.1% of 1783 older solitary people (aged 60–75 years) from the most severely affected disaster area (Dujiangyan, Pengzhou, Shifang, etc.) showed symptoms of depression seven years after the Wenchuan earthquake as measured by the GD Scale-30 (GDS-30).…”
Section: Introductionmentioning
confidence: 99%